The Limits of the Relationship Between Ulama and Umara: An Analysis of the Book Ar-Risalah As-Sultaniyyah by Imam Jalaluddin As-Suyuti - Robi Putra; Abdulloh Azam; Muhammad Al Mighwar; Dadah Dadah (al-Afkar, Journal For Islamic Studies, 2026)
The relationship between ulama and umara is a classic issue in Islamic civilization that has major implications for the moral and social stability of the community. Throughout history, the closeness or distance between these two entities often determines the religious direction and legitimacy of power. Imam Jalāluddīn as-Suyūṭī (d. 911 H) through his work Ar-Risālah as-Sulṭāniyyah emphasized the importance of maintaining ethical boundaries in the relationship between ulama and rulers, especially amidst political situations full of interests. This study aims to uncover the concept of the boundaries of the relationship between ulama and umara according to as-Suyūṭī and its relevance to the context of modern Islamic power. The method used is a library research study with a content analysis approach to the text of Ar-Risālah as-Sulṭāniyyah, complemented by a historical study of the context of Sultan Qāytbāy's reign during the Mamluk period. The results of the study show that as-Suyūṭī emphasized four main principles: maintaining the independence of ulama from political pressure, advising rulers with wisdom and courage, refusing gifts that could potentially tarnish integrity, and placing knowledge as a moral control over power. The conclusion of this study confirms that the ethical concept of the ulama-umara relationship according to as-Suyūṭī is still relevant in maintaining the balance between religious and political authority, and serves as an important guideline for the formation of the character of ulama with integrity in the contemporary era.